Molecular Docking Studies of Spirostans as MAPK14 (P38α) Inhibitors and Their Potential Use against Cancer - Guiee Niza Lopez-Castillo; Victorino Alatriste; Jesus Sandoval-Ramírez; Felix Luna; Alan Carrasco-Carballo (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2021)
Spirostans (SPs) are chemical products widely distributed in the plant kingdom; currently, they are studied by their medical applications. Cancer has a high incidence in humans; it reaches second place worldwide deaths. In molecular biology, it has been accepted that Mitogen-Activated Protein p38alpha Kinase (MAPK14 (p38α) is implicated in the regulation of cancer. This study aimed to identify SPs as potential MAPK14 (p38α) inhibitors. From a set of 133 modified SPs, SwissTargetPrediction platform, and molecular docking, it was obtained that 129 chemical structures had molecular interaction with the MAPK14 (p38α). From those molecules, 123 were bound to a specific inhibition site of MAPK14 (p38α), and 6 of the structures resulted in inhibitors similarly to minocycline and dasatinib. One SP had binding couple energy (BCE, kcal/mol) as that of fostamatinib. In addition, 115 modified SPs had better BCE than the minocycline but not as that using fostamatinib. The key amino acids (aa) for the protein kinase MAPK14 (p38α) inhibition were Arg 70, Asp 168, Lys 53, His 148, and Ile 145, at a different interaction level. The BCE was enhanced when the H atom was substituted in C-2, C-11, and C-17 SPs positions. Similarly, the αOH group at C-5 and C-6 upgraded BCE. Stereochemistry and substitution at C-3, C-12, and C-25 did not present significant differences (Kruskal-Wallis test, p <0.05). From all this ensemble of results, it is foreseeable that the SPs can be an option for MAPK14 (p38α) inhibition, a key modulator in cancer processes.